723 Should Radiation Exposure and Surgeon Safety Be Considered in Decision Making? a Single Centre Retrospective Analysis of Radiation Exposure During Intra Medullary Nailing of Proximal Femur Fractures. (19th August 2022) - Noton, T; Khanom, S; Bagouri, E; Abd Wahab, EH; Vasireddy, A
Abstract: Aim: Short intra medullary (IM) and long intra medullary nails are fixation methods used for proximal femur fractures. Both require fluoroscopic assistance within the operating theatre, therefore exposing the surgeon and patient to ionising radiation. There is minimal literature investigating radiation exposure. Aims of this study are to compare the radiation doses in each procedure and to estimate a normalised dose. Method: Retrospective data analysis was carried out for patients who underwent surgical management of proximal femur fractures with IM nail fixation over a 3-year-period. Data was sourced using electronic operative records and Sectra PACS imaging software. Radiation dose parameters collected were the cumulative dose in milligrays (mGy), cumulative dose area product (DAP) (Gy.cm2) and time of exposure in minutes and seconds. Statistical analysis was performed using SPSS statistical software. Results: A total of 108 patients were included in analysis. 42% were treated with a short IM nail (TFNA - Synthes), while 58% had a long IM nail (RAFN, LFNA or TFNA - Synthes). Mean cumulative radiation dose for the short IM nail group was 7.350mGy versus 10.915mGy for the long IM nail ( P =0.012). Mean exposure time was 01:32 for short IM nail compared to 02:32 for long IM nail. Conclusions: The results confirmed a significant difference in radiation dose and exposure time between both procedures. As the radiation exposure in long nails is almost two-fold, we recommend the use of the short IM nail when the fracture pattern and clinical scenario allow.